The second five year plan - Stephen Grenville (Intereconomics, 1975)
After a short survey of Repelita I, Indonesia's First Five Year Plan, the author reviews Repelita II, Although this Second Plan's broad strategy remains much the same as of Repelita I, its emphasis is on problems recognised but not yet overcome, e.g. those of income policy, job creation, regional development, education, etc.
Keywords: 330; Indonesia